A study on prevalence of ecto- and endo-parasitic infection of cattle at Savar, Dhaka (Bangladesh Journal of Livestock Research, 2020)
A prevalence study was conducted to observe both ecto-and endo-parasitic (gastrointestinal) infection throughout one year surveillance. The study was conducted from July 2014 to June 2015 through Parasitology Laboratory, BLRI, Savar, Dhaka. The study considered age of cattle, season and type of parasitic infestation. In the study area total number of cattle population was 2000 in which 500 fecal and 200 ectoparasitic samples was collected considering three respective seasons like rainy, summer and winter. The fecal samples were examined by direct smear method followed by McMaster counting techniques and examine under microscope. After collection of samples within 24 hours all sample were tested by preserving at 40C temperature. In clinical observation, the overall prevalence of endoparasitic (gastrointestinal) infection was 68% and ectoparasitic infection was 60%. Prevalence of endoparasite was more frequent in rainy season (52.65%) followed by summer (27.05%) and winter season (20.29%) whereas prevalence of ectoparasite was more frequent in summer (39%) followed by rainy (13.5%) and winter (7.5%) season. The parasitic prevalence load was low in winter season. In endoparasitic infection, the higher prevalence of Paramphistomum spp. (20%) was found in rainy season whereas Haemonchus spp. (14%) and Toxocara spp. (12%) were higher in summer. In cattle, prevalence of Paramphistomum spp. (25.14%) and Haemonchus spp. (18.58%) was higher in adult cattle (above 6 months), whereas prevalence of Toxocara spp. (36.67%) and Coccidial oocyst (23.33%) was higher in calf (under 6 month) than adult animal (above 6 months) of age. The overall prevalence of ectoparasite was 60% and tick infestation was highest (22.5%) followed by lice (17.5%), mange (12.5%) and maggot fly (7.5%). High humidity (above 70%) and temperature provoke high endo- and ecto-parasite infection in the environment and infect cattle as well as other livestock species.Bangladesh J. of Livestock Res. 21-25: 29-35, 2018